Implementasi Pembiasaan Membaca Al Qur’an Terhadap Sikap Spritual Religius Siswa - Maria, Anly; Ahmad, Saepudin (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
Students' religious spiritual attitude is the ability of students to behave both vertically to Allah SWT. or vertically to fellow humans and nature.  The inability to behave and think which is also not based on religious teachings will have an impact on life patterns / habits that are far from the happiness of the world and the hereafter. Therefore, it is necessary to carry out the habituation of reading the Koran as a stimulus in shaping students' religious spirituality. Therefore, the purpose of this research is to describe how the impact of reading the Qur'an on students' religious spiritual attitudes. The research method used is a descriptive qualitative approach which aims to describe conditions based on actual conditions in the field. Data collection is done through interviews, observation, and documentation. Data validity is done through data triangulation. Meanwhile, the analysis was carried out through data collection, data reduction, and conclusion making. The results showed that the habit of reading the Qur'an on the spiritual attitude of religious students at Mts Al Mukhtariyah Bayongbong Garut has a positive impact on the formation of student character in carrying out daily worship and has the ability to stimulate awareness of the importance of living life based on the concept of education based on religious teachings. Keywords: religious spiritual attitude, habit of reading the Qur'an